Looking at the books: Social accounting of three cassava drying (appropriate technology) cooperative associations in Colombia - Romanoff, S.A. (International Center for Tropical Agriculture, 1985)
The social infrastructure of the farmers` associations on the Northern Coast of Colombia that produce dried cassava chips is analyzed, and the benefits received by both members and nonmembers are indicated. The benefits received by the members vary, depending on the affiliation and the member himself. Political, ideological, and sociological factors affect the no. of beneficiaries. No matter how homogeneous the membership of an association or cooperative is, differential participation can create interest groups within the association that will determine the group cohesion and the use of resources. The lower the price an association pays for cassava, the more the low-sales members benefit from membership, and the higher the price, the more the high-sales members benefit. Low-income members benefit more from wages and profits than from sales. (CIAT)